Ayurveda And Oral Health: A Review - Meena, Shweta; Amrutha, C R; Sakhitha , K S; Sharma, Rajendra Prasad (International Research Journal of Ayurveda & Yoga, 2021)
Oral diseases pose a major health burden for many countries and affect people throughout their lifetime, causing pain, discomfort, disfigurement and even death. Most oral health conditions are largely preventable and can be treated in their early stages. However the conventional treatment options are too expensive considering the fact that most of the oral diseases dis-proportionally affect the poor and socially-disadvantaged members of society There is a global need for alternative preventive and therapeutic options for the management of oral diseases. Ayurveda, the traditional system of medicine of India has an extensive literature regarding the etiopathogenesis and various treatment aspects of Oral diseases. In the present review an attempt has been made to collect and compile the literature pertaining to oral diseases and their treatment in various Classical texts of Ayurveda. It was observed that most of the single herb remedies for oral diseases mentioned in Ayurveda like Yasti madhu (Glycyrrhiza glabra),Triphala etc possess anti-microbial and anti-inflammatory properties which further substantiate their claims. It was also found that Ayurveda focus more on prevention-oriented management of oral disease than treatment-centered practice. Ayurvedic methodologies for maintaining oral health are found to be far more economical, safe and can be easily adopted by the general public.